Comparison of antimicrobial activity of plant tinctures and chemical disinfectants - Kruchynenko, O.; Zamaziy, A.; Petrenko, M.; Lavrinenko, I.; Khyl, A. (Scientific Progress & Innovations, 2025)
Disinfection in veterinary medicine is a complex of measures aimed at destroying pathogens of infectious animal diseases to ensure safe conditions for their keeping and prevent the occurrence and spread of infections. The pharmacological properties of plant extracts are of considerable significance for further research of substances as potential components of preventive veterinary medicinal products. The results of a study on the effectiveness of the following disinfectants are presented in the article: Iodoclean, Virosan, Ioderin, Multiclean Aqua, as well as chamomile and hawthorn tinctures. The antibacterial activity of the alcoholic tinctures and chemical disinfectants was assessed by measuring the zones of micro-organisms’ growth inhibition around the wells containing the test substances, using the agar well diffusion method. The study was aimed at comparing the effectiveness of 40 % chamomile tincture, 70 % hawthorn tincture, and Iodoclean, Ioderin, Multiclean Aqua, and Virosan chemical preparations against the sanitary indicator micro-organisms of Staphylococcus aureus, strain 209 and Escherichia coli, strain 1257.When determining the zone of inhibition of E. coli growth, Iodoclean demonstrated the highest activity with the zone of inhibition of 25 mm. Virosan was somewhat less active (24 mm), which is 1.04 times lower than Iodoclean. Multiclean Aqua and Ioderin disinfectants demonstrated the activity 1.19-1.25 times lower than Iodoclean. Chamomile tincture demonstrated the activity 2.08 times lower, and hawthorn tincture – 3.57 times lower, with the zone of inhibition of only 7 mm. In the study of the inhibition zones against Staphylococcus aureus, Virosan showed the greatest activity with the inhibition zone of 25 mm. Iodoclin and Multiclean Aqua were slightly less active, being 1.08 times lower than Virosan. Ioderin provided the inhibition zone of 22 mm, which is 1.13 times lower than that of Virosan. Chamomile and hawthorn tinctures turned out to be less effective compared to the other disinfectants. Their inhibition zones made 14 and 8 mm, respectively, which are 1.78 and 3.12 times lower than Virosan’s indicators.